1999
DOI: 10.1023/a:1006296729019
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: To accurately characterize the pathophysiology and proliferating activity of oligodendrogliomas, we studied cerebral blood flow and metabolism using positron emission tomography (PET) in five patients with this tumor. Regional cerebral blood flow (rCBF), cerebral blood volume (rCBV), oxygen extraction fraction (rOEF), and cerebral metabolic rates of oxygen (rCMRO2) and of glucose (rCMRGl) were quantitatively measured in tumor lesions and the contralateral gray matter, rCMRGl was analyzed based on both kinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Previous studies have reported perfusion and oxygen metabolism in patients with cerebral gliomas using 15 O-labelled gases PET [ 17 20 ]. The TBF and TBV values varied widely depending on the vascularity of the tumor, whereas significantly decreased TMRO 2 and OEF values were observed in the tumor region compared with normal gray matter or white matter in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported perfusion and oxygen metabolism in patients with cerebral gliomas using 15 O-labelled gases PET [ 17 20 ]. The TBF and TBV values varied widely depending on the vascularity of the tumor, whereas significantly decreased TMRO 2 and OEF values were observed in the tumor region compared with normal gray matter or white matter in the brain.…”
Section: Discussionmentioning
confidence: 99%